Effect of temperature and confining pressure on the evolution of hydraulic and heat transfer properties of geothermal fracture in granite. (15th August 2020) - Shu, Biao; Zhu, Runjun; Elsworth, Derek; Dick, Jeffrey; Liu, Shun; Tan, Jingqiang; Zhang, Shaohe
Highlights: Novel high temperature high confining pressure flow-through experiments and device. Define effect of stress and temperature on hydraulic and heat transfer properties. Define mechanisms of permeability and heat transfer properties evolution. Confining pressure impacts hydraulic response greater than heat transfer behavior. Temperature affects heat transfer behavior more strongly than hydraulic properties. Abstract: The hydraulic and heat transfer properties of artificial fracture networks are key to the efficiency of energy production from geothermal reservoirs. To date, no conclusive view exists of the evolution in fracture permeability and heat transfer coefficient when arbitrary stresses and temperatures are applied. This work examines the evolution of hydraulic and heat transfer properties during simulated geothermal energy extraction using a novel fluid flow-through test device accommodating large single artificial fractures in granite. Experiments are conducted in two contrasting modalities: at constant temperature with increasing confining pressures, and at constant confining pressure with increasing temperature. At constant temperature, as the confining pressure increases from 4 to 20 MPa, both hydraulic and heat transfer properties decrease, with permeability decreases by 46–63% and heat transfer coefficient decreases by 13–67%. Permeability decreases by 28–37% as temperature increases at constant confining pressure larger than 10 MPa, but permeability may first decrease and then increase at low constant confining pressure of 5 MPa. As the temperature increases from 100 to 200 °C at constant confining pressures, heat transfer coefficient increases by 25–45%. Results show that confining pressure impacts hydraulic properties more strongly than heat transfer properties, while reservoir temperature affects the heat transfer properties more strongly than hydraulic properties. These new findings on the evolution of permeability and heat transfer rate for different paths of temperature and confining pressure are critically important to the understanding of heat production from real geothermal reservoirs.